Biocatalytic route to C-4′-spiro-oxetano-xylofuranosyl pyrimidine nucleosides. Issue 6 (2nd November 2018) - Rungta, Pallavi; Mangla, Priyanka; Khatri, Vinod; Maity, Jyotirmoy; Prasad, Ashok K.
Abstract: A facile access to C -4′-spiro-oxetano-xylofuranosyl nucleosides has been demonstrated for the first time through Lipozyme ® TL IM-mediated regioselective acetylation of one of the primary hydroxyl group over the other primary and secondary hydroxyl groups in 3′- O -benzyl-4′- C -hydroxymethyl- β -D -xylofuranosyl nucleosides. Attempts to optimize a convergent route for these spironucleosides via selective manipulation of hydroxyl groups in 3- O -benzyl-4- C -hydroxymethyl-1, 2- O -isopropylidene-α-D -xylofuranose were unsuccessful. Nevertheless; the present linear biocatalytic route efficiently afforded the C -4′-spiro-oxetanoxylofuranosyl nucleosides T and U in 47 and 38% overall yields, respectively, starting from corresponding furanose diol.